2020
DOI: 10.3390/s20030721
|View full text |Cite
|
Sign up to set email alerts
|

A LiDAR Point Cloud Data-Based Method for Evaluating Strain on a Curved Steel Plate Subjected to Lateral Pressure

Abstract: Structural health monitoring (SHM) and safety assessment are very important areas for evaluating the behavior of structures. Various wired and wireless sensors can measure the physical responses of structures, such as displacement or strain. One recently developed wireless technique is a light imaging detection and ranging (LiDAR) system that can remotely acquire three-dimensional (3D) high-precision coordinate information using 3D laser scanning. LiDAR systems have been previously used in geographic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The deflection was estimated and compared between LVDTs. The strain and deformation of a steel plate under lateral pressure using LiDAR data were evaluated by [143]. Through a specific interpolation procedure, the point cloud was converted into a 3D mesh model, and the displacements from the initial shape were computed, followed by the strain calculations.…”
Section: Other Structural Membersmentioning
confidence: 99%
“…The deflection was estimated and compared between LVDTs. The strain and deformation of a steel plate under lateral pressure using LiDAR data were evaluated by [143]. Through a specific interpolation procedure, the point cloud was converted into a 3D mesh model, and the displacements from the initial shape were computed, followed by the strain calculations.…”
Section: Other Structural Membersmentioning
confidence: 99%
“…Jo et al [11] and Jo et al [12] demonstrated that it is possible to approximate displacements across an entire area by approximating the PCD cross-section of a curved steel plate subjected to lateral pressure with a polynomial function and creating a 3D grid model for the entire surface using kriging. This method has the advantage of being applicable even in cases where no measurement targets are available.…”
Section: Introductionmentioning
confidence: 99%
“…Since then field validations have been made by various researchers. [45][46][47][48][49] Depending on hardware specification, some Lidars are known to have long-distance measurement and high precision ranging 3-5 mm. 50,51 However, those precise Lidars require a long scanning time and adjustment processes, resulting in their popular usage in geomatics and static measurements and limited application in dynamic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The first attempt for measuring the static deformation of a structure using a Lidar was made by Park et al 44 When compared with LVDT, the Lidar showed a maximum error of 1.6%. Since then field validations have been made by various researchers 45–49 . Depending on hardware specification, some Lidars are known to have long‐distance measurement and high precision ranging 3–5 mm 50,51 .…”
Section: Introductionmentioning
confidence: 99%